1969
DOI: 10.1128/jb.98.2.827-828.1969
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma laidlawiiin Human Burns

Abstract: Mycoplasma laidlawii was recovered from burns from 13 of 52 patients. In most cases, cocci or bacilli were isolated simultaneously. Mycoplasma species have been isolated from a variety of animals including man, but no reports have been found of the presence of this organism in human burns. The following note deals with the isolation of a Mycoplasma species identified as a strain of M. laidlawii. Original isolation of strains of M. laidlawii was made from sewage (5), but more recently these organisms have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

1971
1971
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…Studies have shown that M. gallisepticum induced a more severe disease during dual infection with viruses in avian hosts (19,32). Pertinent to our results, A. Iaidlawii has been isolated directly from the human oral cavity (33), leukemic bone marrow (18), and human burns (29). However, this organism has not as yet been examined with regard to its interaction with viral infections in humans and other animals.…”
Section: Min (V) Activity Against Both Vsv and Sindbis Viruses In Flsupporting
confidence: 71%
“…Studies have shown that M. gallisepticum induced a more severe disease during dual infection with viruses in avian hosts (19,32). Pertinent to our results, A. Iaidlawii has been isolated directly from the human oral cavity (33), leukemic bone marrow (18), and human burns (29). However, this organism has not as yet been examined with regard to its interaction with viral infections in humans and other animals.…”
Section: Min (V) Activity Against Both Vsv and Sindbis Viruses In Flsupporting
confidence: 71%
“…The saprophytic strain M. laidlawii (75), now reclassified as Acholeplasma laidlawii because of its nonrequirement for sterols for growth, and other sterol nonrequirers such as A. granularum (196) and as yet unclassified species (197,198) are becoming increasingly common cell-culture contaminants. The nonhuman origin of these mycoplasmas raises questions as to the source of these contaminants, although the degree of host specificity of mycoplasmas is itself in question since swine mycoplasmas (75) and A. laidlawii (75,110,149) have been isolated directly from human clinical material. Constitutents of cell-culture medium, such as serum and trypsin, have been frequently tested for the presence of mycoplasmas, with negative results.…”
Section: Sources Of Mycoplasma Contami-mentioning
confidence: 99%
“…1 serologically distinct human Mycoplasma strains and one strain of A. laidlawii A (PG-8). The latter serotype was included because it has been isolated occasionally from humans (8,11).…”
Section: Resultsmentioning
confidence: 99%